Foscarnet as treatment for cytomegalovirus retinitis following bone marrow transplantation. Issue 751 (May 1988) - Ganly, P. S.; Arthur, C.; Goldman, J. M.; Schulenburg, W. E.
Abstract : This report describes a patient with chronic granulocytic leukaemia who developed cataracts on busulphan treatment. Following allogeneic bone marrow transplantation, he developed cytomegalovirus retinitis, which was treated successfully with trisodium phosphonoformate (foscarnet). Cytomegalovirus retinitis and its therapy, and busulphan-induced cataract are discussed.